Detection of the Virulence Gene Chro.20010 for a Parasite Cryptosporidium Spp - Al-Salami, Abdullah Hussein; Muhaimeed, Abdulkhaleq Alwan; Mahmoud, Anas Yassin (American Journal of Bioscience and Clinical Integrity, 2025)
General Background: Cryptosporidium spp. is a globally distributed protozoan parasite responsible for cryptosporidiosis, a diarrheal disease affecting both immunocompetent and immunocompromised individuals. Due to the absence of highly effective treatments, molecular studies are crucial for understanding the parasite’s virulence mechanisms. Specific Background: The heat shock protein (Hsp70), encoded by the Chro.20010 gene, plays a pivotal role in parasite survival under stressful conditions. However, its structural and genetic characteristics remain inadequately explored. Knowledge Gap: Previous studies have identified Hsp70 as an essential chaperone protein in various pathogens, but limited research has analyzed its molecular structure and role in Cryptosporidium hominis. Aims: This study aims to investigate the presence and structural properties of the Chro.20010 gene in Cryptosporidium hominis isolates to evaluate its potential as a diagnostic and therapeutic target. Results: The gene was successfully amplified in 89% of positive stool samples using Nested PCR, confirming its prevalence. Sequence analysis revealed a conserved structure with no mutations, indicating its genetic stability. Structural modeling demonstrated the functional domains of Hsp70, particularly the nucleotide-binding and substrate-binding regions, which contribute to protein stabilization under stress. Novelty: The findings highlight the molecular stability and functional importance of Hsp70 in Cryptosporidium hominis, reinforcing its role as a virulence factor and potential therapeutic target. Implications: This study provides foundational insights for future research targeting Hsp70 as a drug candidate, potentially aiding in the development of novel therapeutic strategies against Cryptosporidium infections.